Legal Review of Trademark Rights Infringement on Football Club Merchandise Plagiarisme - Gabriel Brillian Dwi Pantara; Rizky Prada Putra Santoso; Ryan Dwi Firmansyah; Nuril Fatimatus Zahro (Indonesian Journal of Sports Law, 2024)
Sport is an activity to regularly train and move body parts that must be carried out by every human being. It is important to do exercise to maintain health and fitness. One of the sports that is a favorite among the people is football. This is none other than because football is a sport that is easy to play and can unite various groups. It is not only a sporting event of choice to maintain health. Currently, football has also become a quite popular industry among various groups, both artists and local entrepreneurs. In fact, this game can be said to be the most popular. The high public interest in football certainly has an impact on the economic and creative fields. Where various football events have indirectly provided great opportunities for artists and local merchandise entrepreneurs to be able to develop their businesses. However, unfortunately, apart from providing positive opportunities, industrial developments in the sport of football have also had a negative impact on a number of groups. Namely in the form of increasingly high levels of plagiarism on other people's merchandise brands. This research was carried out with the aim of finding out the impacts of plagiarism on artists and local entrepreneurs who create merchandise.